PENGUATAN BAGI PELAJAR TERHADAP ANCAMAN BAHAYA PENYALAHGUNAAN NAPZA DI DESA REJOSARI LAMPUNG SELATAN - Bambang Hartono; Zainab Ompu Jainah; Erlina B; Hendri Dunan; Intan Nurina Seftiniara; Suta Ramadan (LP4MK STKIP PGRI Lubuklinggau, 2022)
Teenagers are the nation's next generation of young people in globalization in the era of the industrial revolution 4.0, where teenagers are required to be able to follow the transition to the millennial modernization era. The threat of the dangers of abuse of Narcotics, Psychotropics, and Addictive Substances (Drugs) in Indonesia is now increasingly prevalent, so it is increasingly worrying that drug abuse can increase from various circles of society, including teenagers who are still good students who are still in junior high school to high school. There are various reasons why students or students engage in deviant behavior such as drug abuse, namely: 1) the use of drugs in the social environment, especially in the association of teenagers, is considered normal and even becomes a modern trance, 2) begins with the persuasion of friends to try to feel the effects. of these drugs, 3) there is an excessive pressure of life burden so that a person is stressed and a desire arises to feel his pleasure for a moment, and 4) a user has an addiction so that he feels he can't stop. Increasing students' awareness and knowledge of the dangers of the threat of drug abuse must be done from an early age. The importance of providing education about the dangers of drugs to students in the school environment is the first step to prevent students from falling into juvenile delinquency, because teenagers are the nation's next generation of young people, which must be protected from drug abuse.